A review of the cysts of the spleen. Issue 12 (December 2016) - Khan, Zanobia; Chetty, Runjan
Abstract: Cystic lesions of the spleen are relatively uncommon and often incidental findings. Given the rarity of these lesions, when encountered clinically, a wide range of differential diagnosis are considered. This review highlights the spectrum of neoplastic and non-neoplastic cystic lesions of the spleen and summarizes the pathogenesis, clinical presentation, key radiologic and histopathological features, associated complications and various available treatment options. Cystic lesions of the spleen can be classified broadly as non-neoplastic (pseudocysts, congenital, infectious or vascular cysts) and neoplastic (primary or metastatic cystic neoplasms). With frequent use of abdominal imaging techniques such as ultrasonography (US) and computed tomography (CT), the detection of splenic cysts has increased. Total splenectomy has been the preferred treatment for large, multiple, deeply located splenic cysts. However, because of immunologic role of the spleen and increased risk of post-splenectomy infections, currently spleen-preserving minimally invasive procedures have been advocated for superficially located splenic cysts, especially in children and young adults.